Defect localization by an extended laser source on a hemisphere - Daniel Veira Canle (Nature Portfolio, 2021)
Abstract The primary goal of this study is to localize a defect (cavity) in a curved geometry. Curved topologies exhibit multiple resonances and the presence of hotspots for acoustic waves. Launching acoustic waves along a specific direction e.g. by means of an extended laser source reduces the complexity of the scattering problem. We performed experiments to demonstrate the use of a laser line source and verified the experimental results in FEM simulations. In both cases, we could locate and determine the size of a pit in a steel hemisphere which allowed us to visualize the defect on a 3D model of the sample. Such an approach could benefit patients by enabling contactless inspection of acetabular cups.